Different treatment of hate speech in the process of communication in Europe and the U.S. - Živanovski, Nenad (CM: Communication and Media ISSN 2466-541X; 2466-5452 (Online), 2014)
The question how to treat the hate speech in the communication process is complex and there is no easy answer. Two existing models - American and European - are entirely different towards hate speech and its positioning in the room that belongs on the freedom of expression. In the American legal system, hate speech is an integral part of freedom of expression, while in Europe it is an abuse of the basic human rights for free speech. Hence, in these two approaches permanently is present the issue is there any limit in democracy for freedom of expression and if so, where to draw the line. The dilemmas are not easy to solve and there is no universal answer: sometimes and the best intentions to prevent the spread of hatred in the communication processes could be easily stray into a ban with totalitarian character of a different opinion and criticism; On the other hand, and excessive openness for different views and perspectives in society could be deformed in the abuse of the right for free speech and losing of sense of responsibly for publicly spoken speech and harming of another one. Unfortunately, the state does not have a universal "instrument" that would show whether something is freedom of expression or its misuse. This is a question that American and European legislation attempting to answer for a while, however without definite conclusion and universally acceptable solution. Key words: hate speech, free speech, discourse, media, law, government